Brain Metastases Research 1990–2010: Pattern of Citation and Systematic Review of Highly Cited Articles - Carsten Nieder; Anca L. Grosu; Minesh P. Mehta (The Scientific World Journal)
Background. High and continuously increasing research activity related to different aspects of prevention, prediction, diagnosis and treatment of brain metastases has been performed between 1990 and 2010. One of the major databases contains 2695 scientific articles that were published during this time period. Different measures of impact, visibility, and quality of published research are available, each with its own pros and cons. For this overview, article citation rate was chosen. Results. Among the 10 most cited articles, 7 reported on randomized clinical trials. Nine covered surgical or radiosurgical approaches and the remaining one a widely adopted prognostic score. Overall, 30 randomized clinical trials were published between 1990 and 2010, including those with phase II design and excluding duplicate publications, for example, after longer followup or with focus on secondary endpoints. Twenty of these randomized clinical trials were published before 2008. Their median number of citations was 110, range 13–1013, compared to 5-6 citations for all types of publications. Annual citation rate appeared to gradually increase during the first 2-3 years after publication before reaching high levels. Conclusions. A large variety of preclinical and clinical topics achieved high numbers of citations. However, areas such as quality of life, side effects, and end-of-life care were underrepresented. Efforts to increase their visibility might be warranted.